Relationship Fear Of Missing Out With Social Media Addiction High School-Aged Teens - Nur Azizah Kamaruddin; Harianti Haris; Nurlina (Comprehensive Health Care, 2022)
Fear of Missing Out (FOMO) can be known if a person has feelings of anxiety, worry, loss, discomfort, and stress that arise when knowing others are doing something fun and we are not involved in it, this FOMO syndrome arises because of an addiction caused by a lack of control from the individual in accessing social media that causes a person to experience dependence. The purpose of this study is the known relationship of FOMO with social media addiction in high school-age teenagers end of grade XI at SMKN 1 Bulukumba in Bulukumba Regency in 2020. This research uses cross-sectional research methods. This study sample of 52 with sampling techniques was done with nonprobability sampling technique, namely purposive sampling. The data analysis in this study uses a chi-square statistical test. The results of the analysis using chi-square statistical tests. with a level of trust (=0.05 )based on the results of this test obtained the value of p is 0.002 thus p < (0.002< 0.05), Ho is rejected and Ha is accepted. The conclusion of this study is that there is a link between FoMO and social media addiction in high school-aged teenagers at the end of grade XI at SMKN 1 Bulukumba in Bulukumba Regency in 2020. Researchers suggest that the results of this study can be used as a reference for application in the scope, especially for teenagers in using social media and nursing services, especially mental individuals who experience addiction.